Work-Related Musculoskeletal Symptoms in Ground Handling Crewsat Mutiara Sis Al-Jufri Airport - Aji, Muhammad; Cornelis, Leonard Crystianmars; Syahrir, Muhammad Sabri; Rau, Muhammad Jusman; Hilintang, Rendhar Putri (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Musculoskeletal disorders are conditions characterized by symptoms ranging from mild discomfort to severe pain in the musculoskeletal area caused by improper work practices. Musculoskeletal complaints affect approximately 1.71 billion people globally and are the leading cause of disability worldwide. Improper manual material handling, such as incorrect lifting and carrying techniques, can exacerbate musculoskeletal symptoms such as pain, discomfort, and sleep disturbances, ultimately reducing productivity—particularly among airport ground handling personnel. Several factors, including age, working posture, body mass index (BMI), and length of employment, may contribute to these complaints. This study aimed to examine the association between age, working posture, BMI, and years of service with musculoskeletal complaints among ground handling workers at the apron area of Mutiara SIS Al-Jufri Airport, Palu, in 2025. A quantitative approach with a cross-sectional study design was employed, involving 41 ground handling personnel selected using a total sampling technique. Data analysis using chi-square and Fisher’s exact tests revealed significant relationships between working posture (p = 0.015) and years of service (p = 0.021) with musculoskeletal complaints, while age (p = 0.130) and BMI (p = 1.000) showed no significant association. It is recommended that workers communicate effectively with their team to distribute workloads, maintain an ideal body weight, implement job rotation, and maintain proper posture when handling materials.